Improving Pre-Service Science Teachers’ Content Knowledge and Argumentation Quality through Socio-Scientific Issues-Based Modules: An Action Research Study - Nurcan Tekin; Oktay Aslan; Süleyman Yılmaz (Universitas Pendidikan Indonesia, 2020)
This paper aimed to assess improvements in content knowledge and argumentation quality of pre-service science teachers (PST) through a socio-scientific issues-based (SSI-based) module course. The study was designed as action research with 25 PSTs. Data collection instruments were an energy-related content knowledge questionnaire and video recordings. An energy-related content knowledge rubric was used to evaluate the content knowledge of PSTs, while their argumentation quality was analyzed using a video analysis inventory. The module course was completed in eight weeks. Findings showed that the SSI-based teaching modules course improved energy-related content knowledge with all PSTs increasing by a minimum of one criterion on the rubric. Although the number of arguments decreased weekly, the argumentation quality also increased. Thus, it can be inferred that SSI-based module teaching is a practical tool to teach energy-related content knowledge and argumentation qualities. The study suggests that action research can contribute to developing an effective learning environment. Further studies that include the actual practices of PSTs as they reflect and revise their learning are indicated.